Distributed compressed video sensing with multiple key frames - Mizuki Nomaguchi; Ryota Inoue; Kuntpong Woraratpanya; Yoshimitsu Kuroki (My University, 2026)
Distributed Compressed Video Sensing is a video compression method utilizing Compressed Sensing and Distributed Video Coding. With this method, compressed frames are reconstructed with information obtained by applying Convolutional Sparse Coding to a non-compressed frame. In this study, we aim to increase the reconstruction accuracy by selecting multiple non-compressed frames. In addition, we use symmetric convolution in order to solve a high computational optimization problem. The experimental results show our proposed method outperforms the conventional method.
Keywords: Sparse and Compressive Sensing Techniques; Distributed Sensor Networks and Detection Algorithms; Energy Efficient Wireless Sensor Networks